KERAGAAN PEMBIAYAAN USAHATANI TEMBAKAU BESUKI Na Oogst - -, SUGIARTO; SYUKUR, MAT (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
The necessity of capital for the community in village, especially for tobacco Besuki Na Oogst farmer is very important to sustainable farm. Nevertheless, the problem of low capital will always appear to increase farm and income. So that, the research that give information about financing farm performance tobacco Besuki Na Oogst. Research show after the end PRPTE project, the access of tobacco farmer to get credit which comes from formal institution financing, in fact that it doesn’t give any credit for tobacco farmer. Besides that, the frequency of borrowing and values are still low. At first, cost of transaction is expected to become burden for the credit; it doesn’t have any influence to the borrower. It is because the screening, delivery, and the pattern of incentive, also enforcement, application form which has been applied by formal financing institution is good enough and easy to understand by the farmer who wants to access them. Although tobacco farmer aspiration to the formal institution financing which is expected without difficult procedure, on time, exact in the quantity but also with requirement for borrowing application which is cheap. To make it cheap and easy for farmer to access formal institution financing, that will be better if make Micro Finance Institution (Lembaga Keuangan Mikro) in the village which can bridge the credit for agriculture. In this condition we hope that it can solve the limits of capital and it can increase farm agricultural and society income.
Keywords: Performance, Financing, Farm, Tobacco, Besuki Na Oogst